Comparison of High Capacity SVC and STATCOM in Real Power Grid - Ding Lijie; Liu Yang; Miao Yiqun (2010 International Conference on Intelligent Computation Technology and Automation, 2010)
Both SVC (Static Var Compensator) and STATCOM (Static Synchronous Compensator) are important equipment of reactive compensation, which are compared in voltage supporting, improving the transient stability and transmission limit, and damping low frequency oscillation. Simulation results are presented as high capacity static var system for SVC or STATCOM is placed on transmission path of power system. Firstly, single SVC and STATCOM are limited in voltage supporting after fault occurrence, but STATCOM is little better than SVC. Secondly, STATCOM is much better than SVC in improving the transient stability and transmission limit. Thirdly, on the damping low frequency oscillation, STATCOM is much better than SVC as SVC and STATCOM have the same capacity, and performs similarly with SVC as the two have the same controllable capacity. Lastly, the results also indicate that dynamical response speed effects the control result little though STATCOM responses much faster than SVC.